EQUAÇÕES TRADICIONAIS E SIMULTÂNEAS PARA BIOMASSA DE COMPARTIMENTOS AÉREOS DE CRYPTOMERIA JAPONICA (L.F.) D. DON. - COUTINHO, Vinicius Morais; SANQUETTA, Carlos Roberto; SANQUETTA, Mateus Niroh Inoue; RODRIGUES, Aurélio Lourenço; CORTE, Ana Paula Dalla (Brazilian Journal of Biometrics, 2017)
The aim of this paper is to develop mathematical equations for the prediction of both the total individual aerial biomass and the following compartments: stem with bark and canopy for Cryptomeria japonica (L.F.) D. DON. In addition, in order to guarantee additivity between biomass compartments, a system of apparently unrelated equations (SUR) or simultaneous equations system was fitted. Using the destructive method, 34 trees were planted and weighed from an experimental plant located in the municipality of Rio Negro, PR, Brazil. The biomass compartmentalization was performed individually, as well as its weighing. Samples were taken to determine the moisture fraction and then determined their dry biomass. We tested 11 traditional models that contained as independent variables the diameter at breast height (dap) and total height (ht). The double input models (d, h) were the ones that obtained the best performance for the total biomass and for the bole biomass. Among the models tested for total aerial biomass, stem biomass and canopy biomass, models 3, 4 and 5, respectively, were the most accurate. The application of the simultaneous equation adjustment method ensured the properties of the additivity between the biomass compartments and the total biomass, avoiding distortions between the sum of the individual equations for each compartment and the total equation.